Multi-objective optimization of CO2 emission and thermal efficiency for on-site steam methane reforming hydrogen production process using machine learning. (20th July 2022) - Hong, Seokyoung; Lee, Jaewon; Cho, Hyungtae; Kim, Minsu; Moon, Il; Kim, Junghwan
Abstract: Currently, hydrogen is produced primarily through steam methane reforming, a gray hydrogen production process that generates CO2 as a by-product. Thus, it is crucial to optimize the process thermal efficiency with minimizing CO2 generation in a hydrogen production process. This study focuses on the multi-objective optimization of low-carbon hydrogen production process, considering both process thermal efficiency maximization and CO2 emission minimization. To this end, a hybrid deep neural network model is developed to increase the robustness of the multi-objective optimization. The developed hybrid deep neural network model is incorporated into a proposed multi-objective particle swarm optimization algorithm that performs Pareto dominance-based multi-objective optimization. In experiments conducted, Pareto-optimal solutions with thermal efficiency distribution between 77.5 and 87.0% and CO2 emissions between 577.9 and 597.6 t/y were obtained. Furthermore, the Pareto-optimal front was analyzed to provide various representative solutions to assist decision-makers. The findings of this study can enable efficient and flexible process operations according to various requirements. Graphical abstract: Image 1 Highlights: Low-carbon hydrogen production from an on-site steam methane reforming process. Multi-objective optimization of thermal efficiency and CO2 emission simultaneously. Multi-objective particle swarm optimization for Pareto dominance-based optimization.